Step 1: {Understanding the Normal Adjustment Condition}
In a refracting telescope under normal adjustment, the total length of the telescope is:
\[
L = f_o + f_e
\]
where:
\( f_o \) is the focal length of the objective lens,
\( f_e \) is the focal length of the eyepiece lens.
Step 2: {Using the Given Values}
It is given that the total length of the telescope is:
\[
f_o + f_e = 30
\]
Also, the magnification of the telescope is given by:
\[
M = \frac{f_o}{f_e}
\]
Since \( M = 2 \), we get:
\[
\frac{f_o}{f_e} = 2
\]
Step 3: {Solving for \( f_o \) and \( f_e \)}
Rewriting the equation:
\[
f_o = 2 f_e
\]
Substituting into the length equation:
\[
2f_e + f_e = 30
\]
\[
3f_e = 30
\]
\[
f_e = 10 { cm}, \quad f_o = 20 { cm}
\]
Thus, the correct answer is \( 20 \) cm.